Experimentelle Kammermusik - Widmann, Jörg 1973- (B.O.A. Videofilmkunst, 2005)
An exploration of three chamber pieces by Jörg Widmann. The disc includes three television programs, originally broadcast in 2004 and 2005 as part of the series Musica Viva : Forum der Gegenwartsmusik on station BR-alpha, featuring performances presented by Musica Viva in Munich. Also included is a full length performance film of each piece, and an interview with the composer taped in 2005.
Interpreten: Stefan Blum [Schlagzeug], Irene Russo [Klavier], Neue Vocalsolisten Stuttgart, Peider A. Defilla [Regie]
Keywords: Widmann, Jörg -- 1973-; Musik; Avant-garde (Music); Percussion music; Piano music; Vocal sextets, Unaccompanied; DVD-Video; Music